The warm Blob in the northeast Pacific—the bridge leading to the 2015/16 El Niño. (19th May 2017) - Tseng, Yu-Heng; Ding, Ruiqiang; Huang, Xiao-meng
Abstract: We address the occurrence of the warm anomaly, known as the Blob, that developed from late 2013 to 2015 in the northeast Pacific and its connection with the El Niño–Southern Oscillation (ENSO) variability. The warm Blob results from the enhanced second ocean–atmosphere (O–A) coupled mode of variability in the tropical and North Pacific, representing a small part of the Victoria mode (VM) in the northeast Pacific forced by the strengthened North Pacific Oscillation-like atmospheric pattern since 2013. We also show that this second O–A mode reflects the meridional variability through the tropical–extratropical teleconnection and is an important precursor to the ENSO variability. The process is confirmed by the coupled patterns that evolved from late 2013 to 2016 and the multi-year persistence of the warm Blob. We emphasize the role of evolving basin-scale VM but not the warm Blob itself prior to the ENSO variability. Hence, the Blob and the most recent 2015/16 El Niño, which differs significantly from the other large El Niños in terms of the triggering hemisphere, are actually linked rather than independent phenomena.